Public folklore - Baron, Robert, 1951-; Spitzer, Nicholas R. (University Press of Mississippi, 2007)
A landmark volume exploring the public presentation and application of folk culture in collaboration with communities, Public Folklore is available again with a new introduction discussing recent trends and scholarship. Editors Robert Baron and Nick Spitzer provide theoretical framing to contributions from leaders of major American folklife programs and preeminent folklore scholars, including Roger D. Abrahams, Robert Cantwell, Gerald L. Davis, Archie Green, Bess Lomax Hawes, Richard Kurin, Daniel Sheehy, and Barbara Kirshenblatt-Gim-blett. Their essays present vivid accounts of public folklor.